Merodiploid Ribosomal Loci Arising by Transformation and Mutation in Pneumococcus - Ravin, Arnold W. (1970)
Merodiploid states have been detected in the ery and str loci of the pneumococcal genome. They are associated with particular mutations (ery-r10 and str-d2) which add to, rather than replace their homologous sites during deoxyribonucleic acid (DNA)-mediated transformation. Markers at linked sites do not become diploid at the same time. The heterozygous condition thus produced is maintained during cell reproduction. However, in the case of the ery merodiploid at least, segregation of haploid types does occasionally occur. The transforming properties of DNA isolated from the merodiploids, taken together with the segregation patterns of the merodiploids, reveal the heterozygous condition. The merodiploid condition can be transferred via a single molecule of DNA, which can be explained by assuming that both alleles at the diploid site are integrated into the linear continuity of the bacterial chromosome. In the case of the ery merodiploid, two distinct, relatively stable but interconvertible states are recognizable. Their interconvertibility, as well as the segregation of hapliod descendants, can be explained as the result of occasional pairing of the duplicated regions with loss of one of these duplicated regions by recombination.